The geopolitics behind the Ukraine conflict: the russian occupation and us interests in Europe: The geopolitics behind the Ukraine conflict: the russian occupation and us interests in Europe (Élisée - Revista de Geografia da UEG, 2022)
On February 24, 2022, the Russian occupation of Ukrainian territory was launched. An issue of extreme complexity that was presented by the Western press manicheistically as the “Putin War”. The media version hides the interests of transnational companies in the energy sector, especially from the United States. Those groups compete with Russian companies in the international energy market. In view of the prevailing misinformation in the western media and the complexity of the issue, the present work presents an analysis of the Ukrainian conflict from the point of view of Political Geography and Communication. This is qualitative research, based on bibliographic analysis, enriched with thematic cartography, created by the authors with ArcGIS.